THE EFFECT OF USING PREDICT,LOCATE,ADD,NOTE (PLAN) STRATEGY ON THE STUDENTS’ READING COMPREHENSION OF ARGUMENTATIVE TEXTS - Mira Dwi Samtami and Anni Holila Pulungan (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2016)
This study was aimed at finding out the effect of using Predict,Locate,Add,Note (PLAN) Strategy on the Students’ Reading Comprehension of Argumentative Texts. This study ased the experimental design. The population of this study was the students of SMA Negeri 14 Medan. There were sixty students as the sample of research. This study was conductedwith two randomized group. Namely experimental and control group. The experimental group was taught by Predict,Locate,Add,Note (PLAN) Strategy while control group was taught without Predict,Locate,Add,Note (PLAN) Strategy. The instrument of collecting the data was multiple choice test which consists of 25 items. To obtain the reliability of the test, the researcher used Kuder Richardson (KR-20) formula. The calculation shows the reliability is 0.83 (very high). The data were analyzed by using t-test. The calculation show that t-observed (6.5) is higher than t-table (2.00) at the evel of significance (x)0.05 with the degree of freedom (df) 58. Therefore, the null hyphothesis (Ho) is rejected and alternative hyphotesis(Ha) is accepted. It means that teaching reading comprehension of argumentative texts by Predict, Locate, Add, Note (Plan) Strategy has more significant effect than teaching reading comprehension of argumentative texts without Predict, Locate, Add, Note (PLAN) Strategy.